2004
DOI: 10.1111/j.1365-2672.2004.02216.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of exopolysaccharides by Antarctic marine bacterial isolates

Abstract: Aims: This study was undertaken to examine and characterize Antarctic marine bacterial isolates and the exopolysaccharides (EPS) they produce in laboratory culture. Methods and Results: Two EPS-producing bacterial strains CAM025 and CAM036 were isolated from particulate material sampled from seawater and sea ice in the southern ocean. Analyses of 16S rDNA sequences placed these isolates in the genus Pseudoalteromonas. In batch culture, both strains produced EPS. The yield of EPS produced by CAM025 was 30-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
115
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(125 citation statements)
references
References 45 publications
7
115
3
Order By: Relevance
“…Biologically produced Fe-binding organic ligands are (i) related to alleviation of Fe stress [bacterially-produced siderophores (Rue and Bruland, 1995;Trick et al, 1995;Mawji et al, 2008;Velasquez et al, 2011), the toxin domoic acid produced by the diatom Nitzschia Maldonado et al, 2002)], (ii) retention of episodic iron input (Adly et al, 2015;Westrich et al, 2016), or (iii) ligands produced through biological recycling or basal biological activity such as hemes , ferritin (Castruita et al, 2008), polysaccharides (Ozturk et al, 2004;Hassler et al, 2011a), and EPS (Nichols et al, 2004;Hassler et al, 2011b;Norman et al, 2015). Interestingly, amongst most of these organic ligands, only EPS were reported to contribute to the pool of HS-like substances which is not surprising given that EPS and HS are polyfunctional macromolecules.…”
Section: Organic Ligands Distribution-sources Production and Loss Pmentioning
confidence: 99%
“…Biologically produced Fe-binding organic ligands are (i) related to alleviation of Fe stress [bacterially-produced siderophores (Rue and Bruland, 1995;Trick et al, 1995;Mawji et al, 2008;Velasquez et al, 2011), the toxin domoic acid produced by the diatom Nitzschia Maldonado et al, 2002)], (ii) retention of episodic iron input (Adly et al, 2015;Westrich et al, 2016), or (iii) ligands produced through biological recycling or basal biological activity such as hemes , ferritin (Castruita et al, 2008), polysaccharides (Ozturk et al, 2004;Hassler et al, 2011a), and EPS (Nichols et al, 2004;Hassler et al, 2011b;Norman et al, 2015). Interestingly, amongst most of these organic ligands, only EPS were reported to contribute to the pool of HS-like substances which is not surprising given that EPS and HS are polyfunctional macromolecules.…”
Section: Organic Ligands Distribution-sources Production and Loss Pmentioning
confidence: 99%
“…When grown in batch culture at temperatures near the predicted optimum for this strain, CAM025 produced exopolymer, and chemical analyses showed the purified EPS was composed primarily of neutral sugars (glucose, arabinose, fucose, and galactose), uronic acids (glucuronic acid), and sulfates (29). Sulfates carry a net negative charge at seawater pH (27); uronic acids also contain an acidic carboxyl group that is ionizable in these conditions.…”
mentioning
confidence: 99%
“…Studies of polar sea ice communities using cultivation-dependent and -independent techniques have shown that the "Gammaproteobacteria" are among the dominant taxonomic groupings (6,8,10,35). CAM025 exhibits growth in the temperature range of Ϫ2°C to 30°C, on media containing 1% to 12% (wt/vol) sea salts, and exhibits an enhanced mucoid morphology on marine media with added glucose (29).…”
mentioning
confidence: 99%
“…The excess charge for the highest replicate of WC is also high relative to published values for other organisms, and the values for SC are low (29)(30)(31)34); however, there is (18,22,29). Many bacterial species have been found to increase production of EPS with decreasing temperatures (25,36), although Kiliç and Dönmez (25) found that Micrococcus sp. increases production with increasing temperature.…”
Section: Discussionmentioning
confidence: 89%